A new superfamily and family of Hadziida (Amphipoda: Senticaudata), with a description of a new genus and new species from the Brazilian continental shelf - Alves, Jessika; Lowry, James K.; Johnsson, Rodrigo (Zootaxa, 2020)
A new monotypic superfamily, family, genus and species of Hadziida is described from the Brazilian continental shelf. Magnovioidea superfam. nov. Magnovidae fam. nov. and Magnovis gen. nov. are distinguished by the presence of: antenna 1 shorter than the peduncle of antenna 2; maxilliped outer plate falcate; palp, article 4 reduced and left and right mandibles with a well-developed molar that dominates the mandibular area. Eyes are absent. The type-species Magnovis elizabethae sp. nov. has strongly sexually dimorphic males in which gnathopod 2 is larger than gnathopod 1. Magnovidae fam. nov. occurs on the mid-continental shelf.